Analisa Harga Pokok Penjualan dalam Menentukan Laba pada Rumah Makan Putri Solo “Takana Jo Kampuang” Muara Bulian - Muryati Muryati; Joko Susilo (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study aims to analyze the calculation of the cost of sales as the basis for determining the selling price of the product in determining profit in one period at The Putri Solo Restaurant "Takana Jo Kampuang" Muara Bulian. The method used is descriptive method by using qualitative attachment can also use research to calculate the cost of sales and collect costs that have been spent for the food business. For Return of Business Capital RM with the resulting production capacity. Research shows that Putri Solo Restaurant "Takana Jo Kampuang" Muara Bulian is experiencing stable financial condition and can even achieve maximum results. The cost that has been spent is used as an element of calculation of the formation of the cost of goods sold and the determination of the selling price as the basis in determining the profit of the business. The head of Putri Solo Restaurant "Takana Jo Kampuang" Muara Bulian should maintain and improve their business as best as possible and innovate if they want to keep their business as a developed restaurant.